Effect of Curcumin at Various Doses on the Pharmacokinetic Profile of Tacrolimus in Healthy Rabbits - Issam Mohammed Abushammala; Belal Mohammed Mqat; Abdallah Mohammed Hamdan (College of Pharmacy University of Baghdad, 2022)
The purpose of present study is to evaluate the effect of co-administration of curcumin (CUR) at various doses on the pharmacokinetic (PK) profile of tacrolimus (TAC), a CYP 3A4 substrate in healthy male rabbits. Healthy male rabbits (n=18) were employed in an in vivo, parallel-randomized study. Three groups of rabbits were selected and separated: The rabbits in the first group (control group) received 1 mg/kg TAC orally. Blood samples (1.5-2 mL) were drawn from rabbits' ear marginal veins at the following time frames:  15.0, 30.0, 45.0, 60.0, 90.0, 120.0, 150.0, 180.0 and 300 minutes after TAC administration post dosing and analyzed by using a TAC chemiluminescent enzyme immunoassay (CLIA) detection kit. In the second and third groups (test groups), rabbits received TAC (1mg/kg) at identical conditions as in the control group with volumes equivalent to (30 and 90 mg/kg/day) of prepared CUR suspension in normal saline for seven continuous days. Blood samples from the control group were obtained on the eighth day. Non-compartmental analysis was used to derive different PK parameters of TAC for the three groups. When CUR was co-administered at both concentrations, insignificant statistically small changes between the control and testing groups were found. Our results revealed that the differences for the three groups in PK parameters as Cmax, tmax, ke, AUC0-6 and AUC0-? were statistically insignificant (P>0.05). In conclusion, it has been found that CUR at the experimented doses does not affect the PK of TAC. Further confirmation of our findings is requiered before these results can be applied in patient care.